A preventative lifestyle intervention for older adults (lifestyle matters): a randomised controlled trial - Mountain, Gail; Windle, Gill; Hind, Daniel; Walters, Stephen; Keertharuth, Anju; Chatters, Robin; Sprange, Kirsty; Cook, Sarah; Lee, Ellen; Chater, Tim; Woods, R.; Newbould, Louise; et al. (Oxford University Press, 2017)
Objectives